(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Obesity is a public health problem worldwide, affecting millions of adults each year, and its incidence is increasing, making it the most common problem in women of reproductive age [1]. In women, maternal obesity has been described if their body mass index (BMI) before pregnancy was 30 kg/m2, which has many disadvantages for the mother and fetus, such as high susceptibility to gestational diabetes, hypertension, preeclampsia, congenital anomalies, and intrauterine death [2, 3].